Bolsa família and the citizen's basic income: A misstep? - Tatiana Britto; Fábio Veras Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2011)
This paper discusses the link between Bolsa Família, Brazil's largest direct income-transfer programme, and the citizen's basic income as established in Brazilian legislation. Although these two initiatives were created by law almost simultaneously, the relationship between them does not seem to be unequivocally or even sequentially understood. On the basis of a historical review of their origins, a discussion of their main characteristics, and a survey of bills introduced in Congress on the subject, the paper argues that, despite some commonalities, there are many real and symbolic differences between the formats of conditional cash transfers (CCTs) and basic income. Moreover, legislative proposals submitted to date do not indicate any move towards convergence between the two in Brazil. They represent two different models that coexist within the country's legal framework, without effective transitional mechanisms to ensure the actual implementation of the citizen's basic income law.
Keywords: 330; Transfereinkommen; Soziale Mindestsicherung; Brasilien